Two proteins, one goal: ELISAs based on p32 and L1R for LSDV antibodies detection - Baselli, Stefano; Corsa, Manuel; Bregoli, Arianna; Zanetti, Benedetta; Castelli, Anna; Hoffmann, Bernd; Milovanović, Milovan; Pezzoni, Giulia (Frontiers in Veterinary Science, 2025)
IntroductionLumpy skin disease virus (LSDV), a member of the Capripoxvirus genus, poses a significant threat to livestock health and productivity in both endemic and newly affected regions. The disease is primarily transmitted by blood-feeding insects, leading to fever, cutaneous nodules, lymphadenopathy, and substantial economic losses. While vaccination remains the cornerstone of control efforts, effective surveillance—especially in high-risk areas—relies on robust and scalable diagnostic tools. Although the virus neutralization test is considered the reference standard among serological assays for detecting neutralising antibodies, it is labor-intensive and requires high-containment laboratories.MethodsIn this study, we produced and evaluated two recombinant LSDV antigens: ORF074 (p32), a well-known immunodominant protein, and ORF060 (homologous to the Vaccinia virus L1R), a myristoylated membrane protein identified as a promising immunogenic target. Both proteins were expressed in E. coli. Recombinant p32 was purified under native conditions, whereas recombinant L1R required denaturation and refolding. The antigens were used to develop two indirect ELISAs, and were evaluated using sera from experimentally infected cattle, as well as both vaccinated and infected field samples from Albania and Serbia.Results and discussionBoth assays demonstrated high immunoreactivity and strong concordance with the VNT. These results support the suitability of both antigens for use in serological assays and suggest that a combined, multi-target ELISA approach could enhance diagnostic sensitivity. Once validated for routine use, these novel tools may significantly improve large-scale, cost-effective serological surveillance of LSDV in endemic and at-risk regions.